An efficient fast altitude control for hypersonic vehicle. (July 2020) - Gao, Haitao; Chen, Zhigang; Sun, Mingwei; Huang, Jian; Wang, Zenghui; Chen, Zengqiang
Abstract: It is a challenge to achieve fast altitude control for hypersonic flight due to the inherently insufficient sensitivity of air density to the near-space altitudes. A dominant open-loop feedforward term and a minor altitude error correction term are combined together to obtain the elevation angle command in this paper. A cascade control strategy is used to calculate the elevation command while ensuring the attitude stability. Moreover, an extended state observer is employed to achieve precise and robust attitude control simultaneously, and a stability margin tester is used to tune the controller explicitly. Extensive simulations are conducted to validate the effectiveness, robustness and measurement noise sensitivity of the proposed method. Highlights: An efficient cascade altitude control is presented for hypersonic vehicles. A feedforward term, which triggers no mathematical singularity, plays a crucial role. An extended state observer based attitude control is provided with explicit tuning. Extensive simulations demonstrate the effectiveness and superiority of the proposed method.